THE INFLUENCE OF WIND AND OCEANOGRAPHIC FACTORS ON CHARACTERISTICS OF SUSPENDED SEDIMENT TRANSPORT IN BACH DANG ESTUARY - Vinh, Vu Duy; Uu, Dinh Van (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents some results of applicating three dimension (3D) numerical model to study and assessment influences of tidal oscillation, wind and wave action on characteristics of suspended sediment transport in Bach Dang estuary. Measures data were collected and processed systematically and synchronously  in order to create water river boundary condition (time-serial) for the model. The sea boundary conditions of  model were created by NESTING method. The model was setup with 7 vertical layers in s coordinate. The results of model were validated and calibrated by measured data of water level at Hon Dau, and current velocity and suspended sediment concentration in some points in the model frame. Results of scenarios show the different role of tidal oscillation, wind stress and wave action on suspended sediment transport in Bach Dang estuary. The  tidal oscillations during the flood tide make increasing penetrate of seawater into the rivers from 1-2.5km. It also makes increasing the suspended sediments to the sea from 4-8.0 km during the ebb tide. Under the influences of wind and wave action, the suspended sediments are diffused strongly from bottom to surface layers, the turbidity significantly increases in the area far from the estuary about 10-20km. The wind and wave are main factors creating the  turbidity water zone outside  of Nam Trieu mouth, northeast area of estuary and Do Son beach, especially during the wind and wave in SE direction.